Bowling Alone or Bowling at All? The Effect of Unemployment on Social Participation - Lars Kunze; Nicolai Suppa (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
This article examines the impact of unemployment on social participation for Germany using the German Socio-Economic Panel. We find significant negative, robust and, for some activities, lasting effects of unemployment on social participation. Causality is established by focussing on plant closures as exogenous entries into unemployment. Social norms, labor market prospects and the perception of individual failure are shown to be relevant for explaining these findings. Furthermore, our results not only (i) provide novel insights into the determinants of the unemployed's unhappiness but also (ii) highlight an hitherto unexplored channel through which unemployment influences economic outcomes, namely by altering the long-run level of social capital, and (iii) point to an alternative explanation of unemployment hysteresis based on access to information. – – Dieser Aufsatz untersucht den Einfluss von Arbeitslosigkeit auf soziale Teilnahme in Deutschland mit Hilfe von Daten des Sozio-oekonomischen Panels. Die Autoren finden signifikant negative, robuste und, für bestimmte Aktivitäten, andauernde Effekte von Arbeitslosigkeit auf soziale Teilnahme. Eine kausale Interpretation der Ergebnisse wird durch die Betrachtung von Betriebsschließungen als exogene Eintritte in Arbeitslosigkeit ermöglicht. Soziale Normen, Arbeitsmarktaussichten sowie die Wahrnehmung individuellen Versagens spielen eine wichtige Rolle für die Erklärung dieser Resultate. Zudem liefern die Ergebnisse (i) neue Einsichten in die Determinanten der Lebenszufriedenheit von Arbeitslosen, (ii) betonen einen bisher vernachlässigten Wirkungskanal, durch welchen Arbeitslosigkeit ökonomische Zustände beeinflusst - die Veränderung des langfristigen Niveaus an Sozialkapital - und (iii) deuten auf eine alternative Erklärung für das Phänomen der Arbeitsmarkt Hysteresis, basierend auf einem eingeschränkten Informationszugang, hin.
Keywords: J64; I31; 330; unemployment; social participation; plant closure; fixed effects; well-being